2010
DOI: 10.1111/j.1365-3180.2010.00785.x
|View full text |Cite
|
Sign up to set email alerts
|

Weed communities of transgenic glyphosate‐tolerant soyabean crops in ex‐pasture land in the southern Mesopotamic Pampas of Argentina

Abstract: Postprint (published version

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 23 publications
1
19
0
2
Order By: Relevance
“…(green bristle grass) were the most strongly associated with preceding crop maize, while P. aviculare and C. album preferred other preceding crops. According to Mas et al. (2010), maize as a previous crop also affected weed community structure in soyabean.…”
Section: Discussionmentioning
confidence: 99%
“…(green bristle grass) were the most strongly associated with preceding crop maize, while P. aviculare and C. album preferred other preceding crops. According to Mas et al. (2010), maize as a previous crop also affected weed community structure in soyabean.…”
Section: Discussionmentioning
confidence: 99%
“…These two species can certainly replenish the soil seed banks before stubble ploughing, triggering greater infestations in the subsequent crops. Maize as a previous crop led to an increased proportion of spring germinating weeds in oilseed rape (Hanzlik and Gerowitt 2011), and according to Mas et al (2010), a preceding maize crop also affected weed community structure in soybean. Subbulakshmi et al (2009) also reported significant changes in weed species composition in a maize and sunflower cropping system as a consequence of crop rotation.…”
Section: Preceding Crop and Field Sizementioning
confidence: 99%
“…Large crabgrass (Digitaria sanguinalis) is another species of this genus grown in the Caucasus and Kashmir as a cereal in the past century, but currently known as a widely distributed summer annual weed (de Wet, 1992), even in the glyphosate-tolerant summer crops (e.g. Puricelli & Tuesca, 2005;Dewar, 2009;Mas et al, 2010).…”
Section: Introductionmentioning
confidence: 99%